2018
DOI: 10.1002/etep.2669
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced level-increased nearest level modulation for modular multilevel converter

Abstract: Summary An enhanced level‐increased nearest level modulation (eNLM) method is proposed to improve the performance of modular multilevel converter (MMC) with relatively small number of submodules. The eNLM method can almost double the level number of ac output voltage, compared with conventional NLM. Consequently, the ac output voltage quality of the MMC using eNLM is significantly enhanced. The proposed method inherits the advantages of the conventional NLM such as simple implication and low switching loss and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…And with the exposure of SM to all PWM pulses, the ON and off mode of the SM are equal over N fundamental cycles. These are given by Equation (10).…”
Section: The Mathematical Approach Of Voltage Balancing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…And with the exposure of SM to all PWM pulses, the ON and off mode of the SM are equal over N fundamental cycles. These are given by Equation (10).…”
Section: The Mathematical Approach Of Voltage Balancing Methodsmentioning
confidence: 99%
“…The selective harmonic elimination-pulse width modulation (SHE-PWM) and nearest level control (NLC) are the low-switching frequency methods. [8][9][10][11] In Xin et al, 8 a new approach of SHE-PWM is proposed and generated 2N + 1 levels at load side. However, it has to find the optimal firing angles.…”
Section: Introductionmentioning
confidence: 99%
“…The results show a significantly improved THD, however, the study does not discuss applying the method to a reduced number of levels (less than 21). After a precise review of the literature, it was found that few studies have been conducted on the NLC method applied to the TCHB inverter compared to MMC [22][23][24][25] and asymmetrical CHB MLI [7,21]; Therefore, this paper focuses on applying the NLC method to a 13 level A-TCHB inverter with a DC voltage ratio 1: 2 between two TCHB cells. The method operates at the fundamental frequency and can be extended to any number of levels.…”
Section: Issn: 2088-8694 mentioning
confidence: 99%
“…In [37], output voltage quality can be boosted by combining the NLM and carrier-based PWM method, which causes increase in the switching losses compared with the C-NLM method. e main objective of [38] is to introduce a new NLM method for improving output performance of MMC with increase in the level number. Feasibility of the proposed method is confirmed by simulation results by comparing it with C-NLM for MMC with a large number of SMs.…”
Section: Introductionmentioning
confidence: 99%